Socjopedagogika - studia - szkice - refleksje - wspomnienia - Modrzewski, Jerzy (Wydawnictwo Naukowe UAM, 2016)
Sociopedagogy is a discipline bridging sociology and pedagogy. In the texts in this monograph the author tackles key questions regarding how sociopedagogy has developed since the inter-war period. These questions deal with theoretical aspects, formative research establishing the Polish tradition and the environment within which it is conducted, and also current level of develpment. The sociopedagogy texts in this monograph primarily describe how socialization processes, in their associative and dissociative forms, update themselves dynamically in their socio-cultural contexts, as well as with regard to all age groups in society and the structures they create. It is also an attempt to diagnose social problems experienced in contemporary Polish society, and through examples to highlight the threats: at the individual level, these are threats related to the vital and to customs; at the community level, these are problems infringing the axionormative order practiced and sustained in society, restricting individual citizens’ freedom and existential opportunities.

Socjopedagogika, będąca dyscypliną z pogranicza pedagogiki i socjologii, określana jest także mianem pedagogiki społecznej, względnie socjologii pedagogicznej. W monografii autor podejmuje kluczowe dla jej podmiotowej charakterystyki kwestie kształtowania się od okresu międzywojennego; linie rozwoju socjopedagogicznej refleksji teoretycznej i badań współtworzących jej rodzimą tradycję, środowiska jej uprawiania i stan aktualnego zaawansowania. Przedmiotowe zainteresowania socjopedagogiki, o których mowa w książce, to przede wszystkim aktualizowanie się (w dynamicznie zmieniających się kontekstach społeczno-kulturowych) procesów socjalizacyjnych w ich odmianie asocjacyjnej i dysocjacyjnej oraz odniesionych do wszystkich wiekowych kategorii osób społecznych i współtworzonych przez nie struktur. To również próba diagnozy doświadczanych we współczesnym społeczeństwie polskim problemów zwanych społecznymi oraz wskazania na wybranych przykładach generowanych przez nie zagrożeń: w wymiarze indywidualnym – witalnych i obyczajowych, a wspólnotowym – jako naruszających praktykowany i utrwalany w społeczeństwie ład aksjonormatywny, ograniczających swobody obywatelskie i szanse egzystencjalne.
Socjopedagogy – studies – sketches – reﬂections – memories
Keywords: socjologia wychowania; socjalizacja; uczestnictwo społeczne; problemy społeczne; prizonizacja społeczeństwa; bierność i marginalizacja społeczenstwa